Does Global Liquidity Matter for Monetary Policy in the Euro Area? - Berger, Helge (IMF Working Papers; Working Paper, 2009)
Global excess liquidity is sometimes believed to limit sovereign monetary policy even in large economies, including the euro area. There is much discussion about what constitutes global excess liquidity and our approach adjusts liquidity for longer-term interest rate and output effects. We find that especially excess liquidity in the U.S. leads developments in euro area liquidity. U.S. excess liquidity also enters consistently positive as a determinant of euro area inflation. There is some evidence that this result may be related to a weakening of the effectiveness of monetary policy in the euro area during times of excessive U.S. liquidity.